SOCIAL - PSYCHOLOGICAL CHARACTERISTICS OF INTERPERSONAL RELATIONSHIPS IN WOMEN AFTER CHILDHOOD - Ruzakhon N. Melibayeva; Zulfiya A.Dekhkambayeva; Zarnigor R. Nazarova; Mag’firat M.Abdumutalibova; Umida B.Mirzayeva (The Bioscan, 2024)
This article is devoted to the study of social and psychological characteristics of women before and after childbirth, and the psychological condition of women preparing for motherhood, marital relations, socio-psychological conditions for supporting productive communication between mother and child. The article analyzes thoroughly and explains that the problems of motherhood and childhood are the most important and one of the main strategies of society's development.